サイヒョウ セン シラセ ニ トウサイ サレタ センジョウ ジュウリョク ケイ NIPR-ORI II カタ - 瀬川, 爾朗; セガワ, ジロウ; 神沼, 克伊; カミヌマ, カツタダ; 藤, 浩昭; トウ, ヒロアキ; 福田, 洋一; フクダ, ヨウイチ; 梁, 哲寿; Segawa, Jiro; Kaminuma, Katsutada; Toh, Hiroaki; et al. (1988)
P(論文) 日本南極地域観測隊で使用される新しい船上重力計NIPR-ORI II型について述べる。この重力計はNIPR-ORI I型の改良型であり, 慣性航法級のtuned dry gyro (TDG)が使われている。1987年に東京大学海洋研究所の白鳳丸によって, 最初のテストが行われ, 船速によるエトベス効果の補正をした後の最終的な観測精度は±0.5mgalよりも良いことが確かめられた。 A newly-designed ship-borne gravimeter NIPR-ORI Model II to be used for the Japanese Antarctic Research Expedition is described. This meter is a second version of the previously used NIPR-ORI Model I. The new gravimeter is equipped with the inertial grade gyro called TDG (tuned dry gyro). The first performance test was conducted on board the R/V HAKUHO MARU of the Ocean Research Institute, University of Tokyo in 1987,and it was found that the overall accuracy of the meter after the correction for the Eotvos effect caused by ship's speed was better than ±0.5 mgal. departmental bulletin paper